Frequency of species of Eimeria in females of the holstein-friesian breed at the post-weaning stage during autumn and winter Frequência das espécies de Eimeria em fêmeas da raça holandesa na fase de recria durante o outono-inverno - Fábio Raphael Pascoti Bruhn; Marcos Aurélio Lopes; Fabiana Alves Demeu; Caio Augusto Perazza; Marcos Ferrazani Pedrosa; Antônio Marcos Guimarães (Revista Brasileira de Parasitologia Veterinária, 2011)
The frequency of species of the genus Eimeria in a dairy herd in the municipality of Boa Esperança, Southern region of the State of Minas Gerais was assessed. From 37 females of the Friesian breed aged three to seven months, 259 feces samples were analyzed between May and September 2008. The examinations to quantify oocysts per gram of feces (OPG) and identify Eimeria species were conducted at the Veterinary Parasitology Laboratory of the Federal University of Lavras. Eleven species of Eimeria were identified, namely: E. bovis (23.2%), E. zuernii (22.6%), E. ellipsoidalis (20.3%), E. cylindrica (14.1%), E. subspherica (5.4%), E. canadensis (3.5%), E. alabamensis (2.4%), E. auburnensis (2.4%), E. pellita (2.1%), E. brasiliensis (2%) and E. bukidnonensis (1.9%). E. bovis, E. zuernii and E. ellipsoidalis were the most frequent and the ones with the highest oocyst shedding over time (p < 0.05). Differences in OPG counts were found between most months studied (p < 0.05). The large number of Eimeria species found, in particular E. bovis and E. zuernii, indicates that Eimeria sp. has significant pathogenic potential in dairy cattle in the South of Minas Gerais. Avaliou-se a frequência das espécies do gênero Eimeria em um rebanho leiteiro, criado no município de Boa Esperança, região Sul do Estado de Minas Gerais. Foram analisadas 259 amostras de fezes de 37 fêmeas bovinas, da raça holandesa, com faixa etária compreendida entre três e sete meses, no período de maio a setembro de 2008. O exame para quantificar oocisto por grama de fezes (OPG) e identificação das espécies de Eimeria foi realizado no Laboratório de Parasitologia Veterinária da UFLA. Foram identificadas onze espécies de Eimeria, sendo elas: E. bovis (23,2%), E. zuernii (22,6%), E. ellipsoidalis (20,3%), E. cylindrica (14,1%), E. subspherica (5,4%), E. canadensis (3,5%), E. alabamensis (2,4%), E. auburnensis (2,4%), E. pellita (2,1%), E. brasiliensis (2%) e E. bukidnonensis, sendo E. bovis, E. zuernii e E. ellipsoidalis as mais frequentes e aquelas com maior número de oocistos eliminados ao longo do tempo (p < 0,05). Diferenças na contagem de OPG foram encontradas na maioria dos meses avaliados (p < 0,05). A grande quantidade de espécies de Eimeria encontradas, em especial E. bovis e E. zuernii, indicam um importante potencial patogênico da Eimeria sp. em gado leiteiro no Sul de Minas Gerais.